IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT, SIKAP DAN PERILAKU POSITIF SISWA - Nurul Burhan (UNISAN JURNAL, 2024)
Anticipated objective: To find out and make sense of the endeavors made by teachers in fostering understudies' inclinations, perspectives and positive conduct through character arrangement which at last outcomes in understudies having great ethics in the school climate and in the public eye. To figure out the deterrents that thwart the advancement of kids' advantage in character working at AL Ashriyah Roudlotus Sholihin Center School, Sholihin Region. Bandar Negeri Suoh, West Lampung Rule to figure out how to defeat obstructions that make kids' personality become progressively far off from honorable virtues despite the fact that they have gone to class. In this examination, the creator picked the kind of subjective exploration, to be specific perception, interview or report audit strategies. The explanation is that adjusting this technique is less difficult while managing different real factors, and this strategy presents straightforwardly the idea of the connection among scientists and respondents, and this strategy is more touchy and precise. can adjust to many shared impacts that hone the worth examples experienced. The aftereffects of exploration on the execution of character training in fostering understudies' inclinations, perspectives and positive way of behaving at AL Ashriyah Roudlotus Sholihin Center School, Sholihin Region. Bandar Negeri Suoh, West Lampung Rule are: Ability in planning learning plans, Capability in framing the educational program, Skill in directing assessments. Obstructions in fostering understudies' positive advantages, perspectives and conduct at AL Ashriyah Roudlotus Sholihin Center School are: Low interest in madrasas. There is still low open attention to the presence of Islamic instruction foundations (SMP)